Efforts to Improve Children's Fine Motor Skills through Collage Activities at RA Budi Utomo - Dahniar; Rihanah, Elok (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve children’s fine motor skills through collage activities at RA Budi Utomo. Fine motor development is an essential aspect of early childhood education, as it supports children’s readiness for writing, drawing, and other learning activities. However, observations indicated that many children still experienced difficulties in hand coordination, finger flexibility, and precise movements, which limited their learning performance. To address this issue, collage activities were introduced as a creative and engaging medium to strengthen fine motor skills. The research employed a classroom action research design conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The participants were 20 children aged 4–5 years. Various collage activities, such as tearing paper, cutting, pasting, and arranging materials into creative patterns, were used to stimulate hand–eye coordination and dexterity. Data were collected through observation, performance assessments, and teacher field notes. The results showed that children’s fine motor skills improved significantly after the implementation of collage activities. In the first cycle, only a limited number of children achieved the expected development indicators, while in the second cycle, the majority demonstrated progress in precision, neatness, and independence. These findings suggest that collage activities are an effective method for developing fine motor skills while fostering creativity, concentration, and enjoyment in early childhood learning.